Organizational Culture and Teaching Performance in Public Institutions of Higher Education - Moreno-Bastidas, Galo Ramiro (2021)
Through this research, the aim was to establish the relationship between organizational culture and work performance in the substantive functions of teaching, research and connection with society in the public universities of the Pichincha province (Ecuador). Three universities were selected: University of the Armed Forces (ESPE), National Polytechnic School (EPN) and Central University of Ecuador (UCE). The sample was 304 teachers. To measure and analyze the data, a methodology was established based on the quantitative, qualitative, individual and group characteristics of the existing data. The results show that universities have an organizational culture in which aspects are developed, such as: integration, interpersonal relationships, teamwork and communication. Similar conclusions were obtained from the evaluations: in general, teachers perform adequately in relation to planning, evaluation, content, among others. The correlation analysis developed allowed to demonstrate a significant correlation between the mean values ​​of organizational culture and teaching performance. In this way, the hypothesis was corroborated that the variables of the organizational culture considered do affect the job performance of university professors.